SOCIO-ECONOMIC AND PROFITABILITY ANALYSIS OF RETAILING FROZEN FISH IN RIVERS STATE NIGERIA - Olopade, Olaniyi Alaba; Dienye, Henry Eyina; Anero-Nnamdi, Confidence (University of Islam Malang, 2022)
This study was designed to investigate the socio-economic and profitability of the frozen fish retailing business in Rivers State, Nigeria from March to August 2021. During the study period, a total of 80 frozen fish retailers were selected randomly for this study. Descriptive statistics, budgetary analysis, and multiple regression analysis were used for the analysis. The result of the findings revealed that most (62.5%) of the respondents were within the age range of 31–50 years. A majority (79.5%) of the respondents had acceptable levels of formal education. Results also revealed that fish marketing in the area is dominated by females, with most (70%) of the respondents being married. Most of the respondents had enough experience in fish marketing. The estimate of cost and return analysis shows a net income (NI) of N106, 837.56 per annum. The profitability index was 0.56, indicating that out of every Naira earned, about 56 kobo was returned to the frozen fish retailers as net income. The rate of return on variable cost was estimated to be 29.55%, which means that every Naira spent on variable inputs generates about N30 on a monthly basis, implying improved enterprise profitability. The operating ratio was 0.29, indicating greater total revenue over total variable costs, which is very good for the business, while education and fish quantity sold were positive and significant at 5 percent